Gothic Tradition and the Architecture of Elizabethan Great Country Houses - Savenkova, Alexandra A. (Actual Problems of Theory and History of Art, 2014)
This article concerns the peculiarities of the Elizabethan great country houses architectural style and, above all, its relationship with the local Gothic tradition. This relationship, however strong and fruitful, did not attract suffi cient scientifi c interest. Researchers of the English Renaissance architecture were mainly concerned with the issue of arrival and gradual assimilation of classicism, while the presence of gothic elements was often considered to be inert in its nature. However, there are some strong reasons to believe that such a view is not entirely fair. British architecture of the middle of the 16th c. gives us ex amples of remarkably mature classicism, almost devoid of any Gothic features (Somerset House, Longleat House, the inner court of Burghley House); but during the reign of Queen Elizabeth I a turn towards forms that are strongly associated with the Middle Ages is evident and undeniable. This article attempts to iden tify the causes of this turn, to describe its manifestations and to inquire into its very essence. Through stylistic analysis of the most important houses of the period (and taking into consideration literary documents) the author comes to the following conclusions: 1. The usage of medieval, gothic elements in Elizabethan architecture was hardly stagnant or inert. 2. The stylistic turn which took place in Elizabethan architecture had various cultural and historical foundations. Perhaps sometime it would be interesting to consider Elizabethan style not only as transitional from the medieval to the classical, as precursory to Inigo Jones’s creations, but rather as an attempt of imaginative transformation and re invention of the local Gothic tradition (and such attempts will subsequently appear in England over and over again — from Horace Walpole’s Strawberry Hill to the Westminster Palace).
Keywords: Architecture; England; country house; Renaissance; Gothic